“Modelo de integración y preprocesamiento de información para el descubrimiento de conocimiento en bases de datos federadas utilizando ontologías” - Espinoza Taype, Geovanna Evelyn (2019)
The increase of information in companies has caused an increment of data in her information system, however these hasn’t involved an increase proportional of knowledge available, for get these knowledge is necessary improve in the process of knowledge discovery in databases. The present model propose the use of ontology’s in the first phases in the data mining into to process of knowledge discovery. The advantage more important is the Access to databases heterogeneous through a Homogeneous interface with databases unified and coherent semantically.